Laparoscopic vs. open inguinal hernia repair outcomes in patients aged 65 years and older - Al-Sharabi, Abdulkarem; Xu, Yang; Al-Danakh, Abdullah; Xu, ZhaoHui; Al-Sharabi, Abdullah; Kang, HaoNan; Wen, GuoYi; Shan, Yan; Qu, BoXin; Shao, Shuai; Ren, YanYing; Lee, Juyeong; et al. (Frontiers in Surgery, 2025)
BackgroundInguinal hernia affects approximately 27% of men and 3% of women, with prevalence rising markedly after age 65 due to weakened abdominal walls and comorbidities such as chronic obstructive pulmonary disease and benign prostatic hyperplasia, which increase intra-abdominal pressure. Standard treatment involves surgical repair using either open or laparoscopic techniques. However, the optimal approach for elderly patients remains debated due to higher comorbidity rates and unique physiological considerations. This study compares outcomes of laparoscopic and open inguinal hernia repair in patients aged ≥65 years to support evidence-based surgical decision-making.MethodsWe conducted a retrospective analysis of 384 patients aged ≥65 years who underwent inguinal hernia repair at the Second Affiliated Hospital of Dalian Medical University between 2020 and 2022. Patients were classified into laparoscopic (n = 197) and open (n = 187) repair groups. Demographics, operative details, and postoperative outcomes were compared using chi-square tests, Mann–Whitney U tests, and multivariable logistic regression (SPSS v27), with statistical significance set at p < 0.05.ResultsThe laparoscopic cohort was younger [median 70 (65–91) vs. 75 (65–98) years; p < 0.001], had a higher prevalence of bilateral hernias (25.9% vs. 4.3%; p < 0.001), and smaller hernia sacs [2.50 (1–5) cm vs. 3 (1–5) cm; p < 0.001]. Although operative time was longer for laparoscopy [76 (40–120) vs. 60 (40–115) minutes; p < 0.001], it was associated with fewer postoperative complications, shorter hospital stays, and lower chronic pain rates (all p < 0.01). Multivariable logistic regression identified open repair as an independent risk factor for complications (OR = 0.359; p = 0.012) and chronic pain (OR = 0.258; p = 0.009). Patients in the laparoscopic group also resumed normal activities sooner.ConclusionAlthough laparoscopic inguinal hernia repair requires a longer operative time, it offers superior outcomes in elderly patients, including fewer complications, reduced chronic pain, and faster recovery. Careful patient selection based on age, hernia characteristics, and overall health is essential; however, when feasible, laparoscopy should be considered the preferred approach to optimize outcomes in this population.